MES digital twin - Santos, Diogo Mário Matos dos (2021)
Nowadays, the need to apply the tools of industry 4.0 is increasingly sought, essentially seeking to increase the harmony between workers, machines, and processes, bringing up the concept of Smart Factory. Here lies the digitalization of the shop floor, originating the objective for this project, where it is intended to carry out the simulation of a production line in the simulated environment of Plant Simulation Tecnomatix and integrate with the Manufacturing Execution System (MES) of the company Bosch, Nexeed MES. Therefore, it will be possible to access the production line in advance in this simulated environment, allowing real-time monitoring and simulating any changes and improvements, eliminating costs and excessive time spent unnecessarily. MES are an example of a solution that the evolving industry has been providing for companies. They allow the execution of manufacturing orders in a factory environment, the bridge that connects the shop floor with the enterprise Level (ERP). Tecnomatix introduced by Siemens PLM software, allows the creation of simulation models of a production line or even a company in its entirety. In this project report, a solution was developed that allows the creation of a Digital Twin through the integration of a simulation of the Bosch company MES, Nexeed MES, with a simulation of the production line one of Bosch, in Plant Simulation Tecnomatix environment from Siemens.